Sea-level trends across The Bahamas constrain peak last interglacial ice melt - Dyer, Blake; Austermann, Jacqueline; D’Andrea, William J.; Creel, Roger C.; Sandstrom, Michael R.; Cashman, Miranda; Rovere, Alessio; Raymo, Maureen E. (Proceedings of the National Academy of Sciences, 2021)
During the last interglacial (LIG) period, global mean sea level (GMSL) was higher than at present, likely driven by greater high-latitude insolation. Past sea-level estimates require elevation measurements and age determination of marine sediments that formed at or near sea level, and those elevations must be corrected for glacial isostatic adjustment (GIA). However, this GIA correction is subject to uncertainties in the GIA model inputs, namely, Earth’s rheology and past ice history, which reduces precision and accuracy in estimates of past GMSL. To better constrain the GIA process, we compare our data and existing LIG sea-level data across the Bahamian archipelago with a suite of 576 GIA model predictions. We calculated weights for each GIA model based on how well the model fits spatial trends in the regional sea-level data and then used the weighted GIA corrections to revise estimates of GMSL during the LIG. During the LIG, we find a 95% probability that global sea level peaked at least 1.2 m higher than today, and it is very unlikely (5% probability) to have exceeded 5.3 m. Estimates increase by up to 30% (decrease by up to 20%) for portions of melt that originate from the Greenland ice sheet (West Antarctic ice sheet). Altogether, this work suggests that LIG GMSL may be lower than previously assumed.